Ameliorative Effect of the Oral Administration of Chuquiraga spinosa in a Murine Model of Breast Cancer Induced with 7,12-Dimethylbenz[a]anthracene (DMBA) - Arroyo-Acevedo, J.L. (2020)
Objective: To determine the ameliorative effect of the ethanolic extract of Chuquiraga spinosa (ChS) on 7,12-Dimethylbenz[a]anthracene (DMBA)-induced breast cancer in rats. Methods: 36 female Holztman rats were divided into 6 groups. I) The negative control group received physiological saline (PS). II) ChS-200 group received 200 mg/kg of ChS. III) DMBA group was induced with DMBA (20 mg/Kg) dissolved in PS and administrated orally for 15 weeks. IV) DMBA + ChS-50 group, V) DMBA + ChS-250 group, and VI) DMBA + ChS-500 group, which received the extract orally for 15 weeks after DMBA induction. All data were expressed as mean and standard deviation. One-way analysis of variance (ANOVA) followed by Dunnet test was carried out to compare the mean value of different groups Histopathological analysis was evaluated by using Image J software. Results: Hematology showed that the triglyceride level was significantly lowered (P< 0.01) and high-density lipoprotein (HDL) level was significantly increased (P <0.01) in groups III, IV and V. Also, ChS extract significantly lowered the C reactive protein (CRP) level (P <0.01) and malondialdehyde level (P<0.05). There was a significant decrease in the frequency of DMBA-induced micronucleated polychromatic erythrocyte (P<0.01). Conclusions: Chuquiraga spinosa showed an ameliorative effect on DMBA-induced breast cancer in rats as well as antioxidant, antitumor and antigenotoxic properties.